2007
DOI: 10.1371/journal.ppat.0030165
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Responses to Human Endogenous Retroviruses in HIV-1 Infection

Abstract: Human endogenous retroviruses (HERVs) are remnants of ancient infectious agents that have integrated into the human genome. Under normal circumstances, HERVs are functionally defective or controlled by host factors. In HIV-1-infected individuals, intracellular defense mechanisms are compromised. We hypothesized that HIV-1 infection would remove or alter controls on HERV activity. Expression of HERV could potentially stimulate a T cell response to HERV antigens, and in regions of HIV-1/HERV similarity, these T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
146
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(154 citation statements)
references
References 36 publications
6
146
0
2
Order By: Relevance
“…Early support for the induction of HERV antigen expression in HIV-1-infected subjects was provided by our observation that T cell responses to a variety of HERV-derived peptides are detectable in HIV-1-infected subjects but not in uninfected controls (25,26). Supporting the in vivo relevance of these responses, we observed that strong HERV-specific T cell responses were associated with control of HIV-1 replication (25,27). However, these observations could have resulted from a number of etiologies and are insufficient to either infer HIV-1-induced HERV expression or to validate HERV antigens as novel HIV-1 vaccine targets.…”
Section: Figurementioning
confidence: 96%
See 1 more Smart Citation
“…Early support for the induction of HERV antigen expression in HIV-1-infected subjects was provided by our observation that T cell responses to a variety of HERV-derived peptides are detectable in HIV-1-infected subjects but not in uninfected controls (25,26). Supporting the in vivo relevance of these responses, we observed that strong HERV-specific T cell responses were associated with control of HIV-1 replication (25,27). However, these observations could have resulted from a number of etiologies and are insufficient to either infer HIV-1-induced HERV expression or to validate HERV antigens as novel HIV-1 vaccine targets.…”
Section: Figurementioning
confidence: 96%
“…We have previously presented the hypothesis that the manipulation of the host cellular environment by HIV-1 to one which favors retroviral expression and replication may result in the expression of HERV proteins (25). Following from this, we have speculated that such expression could be targeted by HERV-specific T cells, resulting in the specific elimination of HIV-1-infected cells.…”
Section: Introductionmentioning
confidence: 99%
“…We showed previously that HERV mRNA transcripts and protein are present in the cells of HIV-1-infected patients and that HERV-K (HML-2)-specific T cells can eliminate HIV-1-infected cells in vitro (6,11). In this study, we used a human Ab (HA-137), which recognizes the HIV-1-induced HERV-K (HML-2) TM protein (7), to test for ADCC activity on HIV-1-infected cells.…”
Section: Resultsmentioning
confidence: 99%
“…HERV-K (HML-2), the most recently integrated HERV, was reported to express proteins in some disease states (4,5). During HIV-1 infection, HERV-K mRNA transcripts and viral proteins can be detected in serum (6,7). The mechanisms of interaction between HIV-1 and HERV-K are still under investigation, but the HIV-1 accessory proteins Vif and Tat are thought to play a role in HERV-K protein expression (8,9).…”
mentioning
confidence: 99%
“…They derive from the integration of exogenous, infectiously transmitted retroviruses in the host genomes and are followed by genetic stabilization through accumulation of mutations [4,10]. Under normal circumstances, HERVs are functionally defective or controlled by host factors [9][10][11]. Several types of HERVs belong to the betaretroviruses and gammaretroviruses genera [4].…”
Section: Retrovirusesmentioning
confidence: 99%